God at work on His own lines as seen in various lands in centuries nineteen and twenty - Lang, George Henry, 1874-1958 (Miami Springs, FL Conley and Schoettle, 1985)
Includes bibliographical references.
Brethren writer.
Keywords: Brethren movement -- origins and development